Pemberdayaan Sumber Daya Manusia Dalam Pengembangan Potensi Ekonomi Lokal di Desa Bundar - Sukmaputra, Roni Kurnia; Widyaningsih, Dhina Sri; Sukmani, Meylinda (Syntax Literate, 2025)
This research aims to examine the role of human resources (HR) empowerment in developing local economic potential in Bundar Village, Barito Selatan Regency, Central Kalimantan. Bundar Village has dominant economic potential in rubber commodities and fisheries, supported by village government initiatives in developing the livestock and agricultural sectors. This qualitative research employed in-depth interviews with the village head, community leaders, and youth representatives, supported by document study and SWOT analysis. The results indicate that HR empowerment is a crucial foundation for economic diversification and mitigating the risks associated with rubber price fluctuations. Local wisdom serves as a strong social capital but also presents challenges, particularly social resistance to regulations prohibiting land burning for agriculture, which requires sustainable farming technical solutions. Furthermore, community dependency on aid and the lack of program continuity are major obstacles. An effective empowerment strategy must integrate the enhancement of technical, managerial, and entrepreneurial competencies in alignment with local values (intercropping systems) to create competitive products. Thus, sustainable HR empowerment will strengthen Bundar Village's economic self-reliance and strategically position it as a quality provider of food commodities and services for the IKN Nusantara region.